Auditing the comprehensive electronic banking system to detect operational business risks (applied research) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract:                In light of the development in the banking environment and the increasing reliance on electronic systems in providing banking services and due to the intense competition witnessed by the banking sector, the need has emerged to apply the comprehensive electronic banking system, which works on the Internet in providing new and diverse banking services regardless of time and place by linking all branches to one central database, and despite the advantages achieved from the application of the comprehensive system, there is a set of risks that accompany the use of that system, What requires the auditors to develop the audit method in line with the size of the development in the customer's environment, and from here the research gained its importance by highlighting the reality of the application of the comprehensive electronic banking system in Rafidain Bank and identifying the nature of the external auditor's work in light of the client's application of electronic systems, and thus this research aims to provide a theoretical introduction to the comprehensive banking system, as well as to know the role of the auditor in light of the business risks surrounding the application of the system, The research reached a set of conclusions, most notably, the ability of the comprehensive banking system to develop and adapt banking operations more than other systems, which makes it a global solution for banks in the future due to the importance of the system and its ability to access multiple geographical areas and process operations in real time, and that the lack of preparation of an effective plan in advance for the transformation procedures towards the application of the comprehensive system in terms of providing infrastructure and qualified staffing and studying the problems of transformation and ways to solve them before the actual application of the system led to high operational risks. intrinsic, Therefore, the researcher proposed several recommendations, the most important of which is the need to increase investment in information technology with the development of a division for research and development of banking services provided by the comprehensive system in line with the development in the technological environment and theneeds and desires of customers to provide new and diverse banking services, with the need for the auditor to conduct an audit based on business risks in light of the customer's use of banking systems that rely on the Internet in providing his services, to control the size of current and future business risks that lead to failure Business or material misrepresentations extending to the financial statements.